Interference effects in learning similar sequences of discrete movements - Koedijker, J. M.; Oudejans, R. R. D.; Beek, P. J. (Journal of Motor Behavior, 2010)
Three experiments were conducted to examine proactive and retroactive interference effects in learning 2 similar sequences of discrete movements. In each experiment, the participants in the experimental group practiced 2 movement sequences on consecutive days (1 on each day, order counterbalanced across participants) followed by retention tests on the third day. In all, 2 out of 8 target locations differed between the 2 sequences. Experiment 1 established the nature of the interference effects in the present setup. Clear evidence was found for button-specific proactive and retroactive interference effects. Experiments 2 and 3 further probed the mechanisms underlying those effects, by varying the numbers of repetitions (50 or 250) of the 1st and 2nd sequence (Experiment 2) and the hand, dominant or nondominant, with which the sequences were practiced (Experiment 3). Experiment 2 showed that after a mere 50 repetitions, the representation of the movement structure was strong enough to evoke the effects observed in Experiment 1. Experiment 3 revealed that learning with the dominant hand did not result in more pronounced interference effects compared with learning with the nondominant hand. In combination, these results suggest that changes in the representation of the movement structure are primarily responsible for the observed interference effects.